2013
DOI: 10.1017/s031716710001372x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cognitive Impairment in a Stroke Prevention Clinic Using the MoCA

Abstract: Background:Screening for cognitive impairment is recommended in patients with cerebrovascular disease. We sought to establish the incidence of cognitive impairment using the Montreal Cognitive Assessment (MoCA) in a cohort of consecutive patients attending our stroke prevention clinic (SPC), and to determine whether a subset of the MoCA could be derived for use in this busy clinical setting.Methods:The MoCA was administered to 102 patients. Incidence of cognitive impairment was compared to presenting complaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Third, by retaining category cueing and recognition in the delayed memory, the MoCA 5-min protocol offers important information regarding the type of memory failure that may help to differentiate subtypes of VCI. We showed that when compared to the spontaneous recall score, 4, 7 this modified scoring method correlated better with the MoCA memory domain score. Last, the MoCA 5-min protocol retains a 30-point scoring which allows a broader range of scores for more precise clinical measurement and for statistical analysis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Third, by retaining category cueing and recognition in the delayed memory, the MoCA 5-min protocol offers important information regarding the type of memory failure that may help to differentiate subtypes of VCI. We showed that when compared to the spontaneous recall score, 4, 7 this modified scoring method correlated better with the MoCA memory domain score. Last, the MoCA 5-min protocol retains a 30-point scoring which allows a broader range of scores for more precise clinical measurement and for statistical analysis.…”
Section: Discussionmentioning
confidence: 85%
“…For example, Mai et al showed that a combination of clock drawing, delayed recall and abstraction items performed better than the combination proposed by the NINDS-CSN working group in predicting impaired MoCA performance. 7 However, their version precludes the possibility for telephone administration as drawing is required. Pendlebury et al developed two telephone versions of MoCA (T-MoCA) of different lengths, including a short version that is composed of the set of items recommended by NINDS-CSN working group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] A previous study retrospectively extracted 10-points of the MoCA (5-word recall (5), clock drawing (3), and abstraction (2) and demonstrated strong predictive value for detecting cognitive impairment. [22] We selected this 10-point version of the MoCA (DOC-Cog) to prospectively validate in the stroke clinic population. We integrated the PHQ-2 (DOC-Mood) and STOP questionnaire (DOC-Apnea) into the delay between registration and recall of the 5 word recall task.…”
Section: Methodsmentioning
confidence: 99%
“…55 Screening for cognitive impairment has been recommended in patients with stroke, given results from a recent Canadian study showing that two-thirds of stroke patients have evidence for cognitive impairment. 56 Our findings suggest that identifying people with cognitive impairment may provide an even bigger opportunity to reduce the future burden of stroke through the timely implementation of evidence-based prevention strategies.…”
Section: Fatal Strokementioning
confidence: 81%